Methodology For Developing the Skills Of Working With The Pisa In Future Biology Teachers - Niyozov Qahramon Adashaliyevich (Euro Asian Journal Publishing, 2024)
This article discusses the problems and their solutions in developing the skills of future biology teachers to work under the international PISA program
Keywords: PISA; literacy; competence; context